PENERAPAN KONSEP PARIWISATA HALAL PADA CITRA MEREK PULAU LOMBOK - Lalu Ferdi Ferdiansyah; Sulhaini Sulhaini; Handry Sudiartha Athar (Master of Management, Mataram University, 2020)
This study aims to examine the effect of the application of the halal tourism concept on the brand image of Lombok Island as the island of a thousand mosques on the decision to visit for the millennials tourists at the Mataram Islamic center. The research method uses associative research methods with a quantitative approach. The results of this study indicate that the halal tourism concept variable had a positive and significant effect on the visiting decision variable, as well as the brand image variable which had a positive and significant impact on the visit decision variable, the halal tourism concept variable had a positive yet insignificant effect on the visiting decision. The Mataram Islamic center mosque is an icon of Lombok Island and has been named as the best mosque at the national level in 2020. With the achievements received by the Islamic Center Mataram Mosque, the management must be able to maintain the trust that had been entrusted by the community and tourists. In addition, the West Nusa Tenggara Government needs to carry out more activities to introduce tourist destinations in NTB, especially Islamic center attractions.Keywords:Halal tourism, brand image, visited decision, millennial tourists, Lombok island